Mine Flooding History of a Regional Below-Drainage Coalfield Dominated by Barrier Leakage (1970–2014) - Joseph J. Donovan; Eric F. Perry (Geofluids)
A 44-year record of water level fluctuations in a series of adjacent closed underground mines documents the history of closure and mine flooding in the Fairmont Coalfield, one of the oldest coal mining districts in the Pittsburgh coal basin, West Virginia, USA. As closures proceeded and mines began to flood, US environmental regulations were first enacted mandating mine water control and treatment, rendering uncontrolled surface discharges unacceptable. The purpose of this study is to present this flooding history and to identify critical events that determined how mine pools evolved in this case. Also examined is the strategy developed to control and treat water from these mines. Flooding is visualized using both water level hydrographs and mine flooding maps with the latter constructed assuming mine water hydraulic continuity between one or more mines. The earliest flooding formed small pools within near-surface mines closed prior to 1962 yet still pumped following closure to minimize leaking into adjacent still-active workings. These subpools gradually enlarged and merged as more closures occurred and the need for protective pumping was removed, forming what is today referred to as the unconfined Fairmont Pool. Later, deeper mines, separated by intact updip barriers from the Fairmont Pool, were closed and flooded more gradually, supplied in large part by leakage from the Fairmont Pool. By 1985, all mines except 2 had closed and by 1994 all had fully flooded, with the Fairmont Pool interconnected to deeper single mine pools via barrier leakage. As protective pumping ceased, the Fairmont Pool rose to a water level 3 m higher than surface drainage elevation and in 1997 discharged from an undermined section of Buffalo Creek near the Monongahela River. The principal mine operator in the basin then designed a pumping system to transfer water from the Fairmont Pool to their existing treatment facilities to the north, thus terminating the discharge. It may be concluded that the progress of mine flooding was influenced by mining history and design, by the timing of closures, by barrier leakage conditions, and by geologic structure. A key element in how flooding proceeded was the presence of a series of intact barriers separating deep from shallow mines. The shallow mines closed and flooded early, but then lost sufficient water by barrier leakage into the deeper mines to delay the completion of flooding until after the deep mines had all closed and flooded as well. Intensive mine water control has continued from the 1997 breakout to the present. The final water control scheme was likely unanticipated and serendipitous; future district-wide mining efforts should be advised to consider in advance closeout strategies to control mine water postmining.